2020
DOI: 10.3390/su12145800
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Branding in Retail: A Model of Chain of Effects

Abstract: The main objective of this study is to analyse the impact of sustainable practices on companies’ corporate reputation and brand image in the retail sector as perceived by consumers. In addition, we evaluate how those practices affect consumers’ perceived satisfaction levels and their predisposition to engage in positive Word of Mouth (WOM). For the purpose of this study, the context of an emerging economy, Peru, is taken as reference. To do this, we propose a structural equation model based on a representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Even consumption trends are in favor of companies adopting sustainable and socially responsible modes. Mainstream research [29] revealed that companies with eco-friendly brands, fair management practices, and support for local preferences, experienced far greater sales than those that did not. To recapitulate the above, the benefits of sustainable brand management, so far, include compliance with the United Nations' SDGs, improving brand equity and corporate image, enhancing customer loyalty, and competitive advantage.…”
Section:  You Risk Being Left Behindmentioning
confidence: 99%
“…Even consumption trends are in favor of companies adopting sustainable and socially responsible modes. Mainstream research [29] revealed that companies with eco-friendly brands, fair management practices, and support for local preferences, experienced far greater sales than those that did not. To recapitulate the above, the benefits of sustainable brand management, so far, include compliance with the United Nations' SDGs, improving brand equity and corporate image, enhancing customer loyalty, and competitive advantage.…”
Section:  You Risk Being Left Behindmentioning
confidence: 99%
“…BI refers to the utility or added value that a brand contributes to the product (Flores-Hernández et al, 2020). Armstrong et al (2018) indicated that BI represents what the customer has accumulated in his/her memory about the brand, which is actually what comes to the customer's mind when confronted with the brand.…”
Section: Bimentioning
confidence: 99%
“…To bridge the gap between the rhetoric and reality, it is critical to align the consumers' perceptions of CSR initiatives with the validity of the physical CSR activities carried on by a business (Flores‐Hernández et al, 2020), especially for those organizations which are closer to the market (Haddock‐Fraser & Fraser, 2008). Appropriate communication and translation of CSR initiatives (Bagnoli et al, 2021; Savory, 2006) look essential to make customers understand the real value of activities affecting social and environmental sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Still, the fit between consumers and CSR initiatives (the so‐called consumer‐CSR fit) is critical to ensuring a positive consumer response and engagement to CSR strategies (Moreno & Kang, 2020). Following a similar approach, Flores‐Hernández et al (2020) argue that dedicated CSR policies can boost the brand image, which, as an intangible asset of great value, will reinforce the consumers' decision process and their level of satisfaction regarding the product or service purchased. If companies are capable of generating this virtuous cycle, they can expect positive, non‐transactional behaviours of great value (Gilal et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%